Securing pig health and empowering pig farmers - Milton, Arun Prince; Priya, G Bhuvana; Das, Samir; Ghatak, Sandeep; Sen, Arnab; Laha, R; Deori, S (Indian Farming, 2023)
The objective of the present discourse is to raise awareness among pig farmers about various infectious diseases and disease conditions that can affect pigs. It aims to provide important  information about the signs and symptoms of these diseases as well as strategies for prevention, control, and management. Key topics covered include characteristic signs, vaccination, deworming, and disinfection. By providing comprehensive information on economically important diseases, the discourse aims to empower pig farmers with the knowledge and tools necessary to protect the health and well-being of their pigs and ultimately enhance the productivity and profitability of their pig farming operations.